Examining The Implications Of Maritime Policy On National Defense Strategies - Sarjito, Aris; Ade Wahyuni Azhar (Faculty of Social and Political Science, 2023)
The maritime domain has become an area of increasing importance for global security and defense strategies. Maritime trade accounts for over 90% of global trade, and more than half of the world’s population lives within 60 kilometers of the sea. As such, the maritime domain has significant implications for national defense strategies, including potential threats, prioritizing defense programs, and maintaining a balance between defense and economic interests. The aim of this research is to examine the implications of maritime policy on national defense strategies. The research will address factors including assessing and prioritizing potential maritime threats, coordination and communication between various agencies and governments involved in maritime defense, maintaining a balance between defense and economic interests in maritime policy, the allocation of resources and investment in maritime defense programs, and the effectiveness of maritime defense strategies in achieving their intended outcomes. The research will also explore the changing nature of maritime threats and challenges, the relevance of a strong naval fleet in implementing a country's national defense strategy, the impact of maritime disputes, and the role of new technologies. A qualitative methods approach will be utilized, including a literature review, analysis of government policies and strategies, and interviews with government officials and experts in the field of maritime security. The study will focus on a range of countries with varying levels of maritime interests, including the United States, China, Japan, and Australia. The research findings will provide insights into the implications of maritime policy on national defense strategies and highlight key considerations for policymakers in assessing and prioritizing potential maritime threats, coordinating and communicating between various agencies and governments involved in maritime defense, and maintaining a balance between defense and economic interests in the maritime policy. The research will contribute to the understanding of the changing nature of maritime threats and the role of new technologies in national defense strategies. The limitations of this study are the limited scope of available data on maritime policy and the potential challenges to accurately measure and apply these policies to national defense strategies. In addition, the various interpretations and applications of maritime policy in different countries can further complicate the analysis and generalization of the findings.